The Visible Hand: National Oil Companies, Oil Supply and the Ermergence of the Hotelling Rent - Markus Ludwig (University of Basel, Center of Business and Economics (WWZ), 2012)
Using firm-level panel data, this paper exposes differences in the dynamic oil produc- tion regime between private and state-owned firms. I find that state-owned firms reduce the oil supply, ceteris paribus, by 3.5 percent each year, but private firms hold output constant. Furthermore, state-owned firms have not followed such stringent policy before 1997. My ex- tension of the Hotelling-model attributes the behavior of state-owned firms to a scarcity rent, whereas private firms produce at their constant capacity limit, owing to possible expropriation. The theory also indicates that state-owned firms will only switch to a Hotelling-regime after a certain lag time, attributable to limited capacity. The data further reveals that contractions in the supply of state-owned oil lead to oil price increases, indicating that state-owned firms do, in fact, generate a scarcity rent. My results therefore suggest that the shift from private towards state-owned oil dominance in the 1970s gave rise to a delayed increasing oil price path.
Keywords: Q3; L1; 330; Hotelling-rent; oil supply; national firms; Ölpreis; Produktionskapazität; Vergleich; Öffentliches Unternehmen; Privatwirtschaft; Hotelling-Modell; Welt